Antibody levels in children after 10 years of vaccination against hepatitis B: a brazilian community-based study - Fagundes,Glauco Danielle (2012)
INTRODUCTION: It is known that the hepatitis B (HB) vaccine is effective, but it is alarming that sudden drops of antibody levels may coincide with the onset of adolescence. METHODS: Antibody levels against HB vaccine surface antigen (anti-HBs) and HB vaccine core antigen (anti-HBc) were measured on the blood samples of children with a mean age of 11.4 years. RESULTS: About 54.8% had protective levels of anti-HBs. Of those who were anti-HBc-positive (4.4%), an average of 218.4 anti-HBs mIU/mL was found. CONCLUSIONS: Immunological protection was found in the majority of children. However, more studies are needed to elucidate the heritability of nonresponders and establish strategies against such events.